Pentanuclear Nickel(II) Complex with two Vertex‐Shared Triaminoguanidine Fragments and Symmetric Capping Ligand. Issue 13 (9th July 2020) - Böhme, Michael; Ion, Adrian E.; Kintzel, Benjamin; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract : The pentanuclear nickel(II) complex [Ni5 (saltag Br )2 (tptz)4 ] (Ni5 ) with the tritopic triaminoguanidine‐derived Schiff‐base ligand H5 saltag Br (1, 2, 3‐tris[(5‐bromosalicylidene)amino]guanidine) and tptz (2, 4, 6‐tris(2‐pyridyl)‐1, 3, 5‐triazine) as capping ligands is reported. Ni5 crystallizes in the triclinic space group P 1 with the central nickel(II) ion linking two triangular arrangements of nickel(II) ions supported by two tritopic triaminoguanidine ligands. The octahedral coordination of the four peripheral nickel(II) ions is complemented by capping tridentate tptz ligands. By variation of the synthesis also the corresponding trinuclear nickel(II) complex [Ni3 (saltag Br )(tptz)3 ]NO3 (Ni3 ) is accessible. Magnetic measurements for Ni3 and Ni5 reveal a singlet ground state with antiferromagnetic coupling between the nickel(II) ions, which in the case of Ni5 can only be simulated assuming a two‐ J exchange coupled spin topology. For both complexes significant zero‐field splitting for the nickel(II) ions is evident from the measured magnetic data, which can be verified by theoretical studies revealing a magnetic anisotropy with strong rhombic distortion due to the presence of the tptz co‐ligands in both compounds. Abstract :